Divine Concessions in the Tanhuma Midrashim - Weiss, Dov 1973- (2015)
Ever since Leopold Zunz inaugurated the critical study of rabbinic literature in 1818, scholars of the school of midrash known as Tanhuma-Yelammedenu (TY) have given priority to analyzing questions of textual history, dating, aesthetics, form-critical issues, and the literary qualities of these texts. This scholarship has focused on questions of form rather than content; for the most part, the distinctive ideas of these texts, their values and theologies, have yet to be explored. In an article devoted to form-literary issues in aggadah, Yonah Fraenkel argues that indeed there were also changes in the [Tanhuma's] ideas, like their ethical and social values and their overall world view . . . these types of issues need further research. Unfortunately, very few scholars have responded to Fraenkel's call. In fact, two excellent scholarly works on rabbinic thought have ignored the content of the TY altogether: neither David Kraemer's Responses to Suffering in Classical Rabbinic Literature nor Ishay Rosen-Zvi's recent work, Demonic Desires, engage TY texts. While Kraemer and Rosen-Zvi extensively discuss sixth- and seventh-century Babylonian texts, such as the Babylonian Talmud, they do not do the same with sixth- and seventh-century Palestinian texts, such as many TY texts. These two important studies exemplify how, in a more general sense, late Palestinian midrashim have been conspicuously neglected by scholars of rabbinic literature working on content-based projects.